Socio-environmental conflicts of mining projects in the Arequipa region and its impact on the economy of Peru, 2020 - 2022 - Zevallos-Paredes, Jhon (2024)
The objective was to analyze the socio-environmental conflict of mining projects in the Arequipa region and the impact that it generated on the economy of Peru, during the period 2020 to 2022. It is worth mentioning, which if this refers to the region of Arequipa, where it is located as there mining capital of the country; Accordingly, the region's mining activity contributed an average of 2.98% to the national GDP (Gross Domestic Product); However, there is an active socio-environmental conflict (Tía María mining project) permanent until closure, which generates an economic loss of 0.27% of the national GDP, due to failure to execute; In this context, the impact was negative. The instruments were: surveys and interviews, which covered the variables (Socio-environmental Conflicts of mining projects and Impact on the Economy) with their social, economic and environmental components. The results are: active socio-environmental conflicts generate economic losses, and paralyze public and private investment; Meanwhile, socio-environmental conflicts in dialogue contribute to socio-economic development; guaranteeing governance and social peace; Furthermore, 45% of the population realizes that there is no progress with the mining region and 20% are in agreement with the protest actions because it shows that there is no presence of the State. Finally, we plan for the Peruvian State to implement public policies that guarantee the sustainability of mining in the country.